A Study of the Jose Garcia Villa and Salvador Lopez controversy - Gozum, Christina, B. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1987)
This thesis is the study of the Jose Garcia Villa and Salvador Lopez Controversy. It discusses the issue with a brief historical background on the period it occured, an individual presentation of the writers involved and a balanced analysis of the controversy itself. The background on the period is necessary for the orientation of the reader to its effect on the issue. The individual discussion of the writers is for a better understanding of their respective stands on the controversy. And since the controversy itself is on the subject of poetry, only the works of the writers on poetry have been included in its discussion. The study is a balanced presentation of both writers so that an objective analysis of it may be obtained. The conclusion is then the writer's analysis of the controversy. All views and observations in the end will be this writer's personal analysis of the issue. This will be strictly based on the balanced study done previous to the final conclusion. The study deals only with the period involved, Villa and Lopez and the said controversy. All however, will be dealt with thoroughly and carefully with the help of numerous resources.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references.